A Survey on Unmet Need for Uniform Next-Generation Sequencing Reporting in India - Neha Pathak; Anu R. I.; Padmaj Kulkarni; Amol Patel (Indian Journal of Medical and Paediatric Oncology)
Introduction: Next-generation sequencing (NGS) has paved the way for precision oncology in oncology clinics today. With rapidly advancing therapeutics, it is becoming increasingly important to obtain information about the molecular milieu of a patient's tumor. However, reporting and interpreting of NGS is fraught with complexity and variability. To understand the questions surrounding NGS reporting in India, we conducted a survey.